The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1542/peds.2007-3521
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Sleep Time and Long-Term Risk for Obesity: A 32-Year Prospective Birth Cohort Study

Abstract: These findings suggest that sleep restriction in childhood increases the long-term risk for obesity. Ensuring that children get adequate sleep may be a useful strategy for stemming the current obesity epidemic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
168
5
9

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(193 citation statements)
references
References 42 publications
11
168
5
9
Order By: Relevance
“…[17][18][19][20][21] However, none of these studies investigated whether changes in BMI are associated with changes in sleep duration or studied this relationship during the crucial period of puberty in which sleep duration diverges. We showed, using univariate analysis of variance, that with progressive Tanner stages, BMI increases and sleep duration decreases in an interrelated way, independent of the baseline BMI at start of puberty, FTO allele genotype (rs9939609), BMI of the father and mother, as well as changes during the progressive Tanner stages in Baecke scores and hours television viewing (R 2 ¼ 0.38, Po0.02).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[17][18][19][20][21] However, none of these studies investigated whether changes in BMI are associated with changes in sleep duration or studied this relationship during the crucial period of puberty in which sleep duration diverges. We showed, using univariate analysis of variance, that with progressive Tanner stages, BMI increases and sleep duration decreases in an interrelated way, independent of the baseline BMI at start of puberty, FTO allele genotype (rs9939609), BMI of the father and mother, as well as changes during the progressive Tanner stages in Baecke scores and hours television viewing (R 2 ¼ 0.38, Po0.02).…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15][16] Longitudinal studies have shown that when young children (prepubertally, up to age 12 years) sleep fewer hours per night, they are at a higher risk to become overweight at a later age, during childhood as well as adulthood. [17][18][19][20][21] Sleep duration during childhood, however, naturally decreases, in particular during puberty when a reduction of about 2 h is observed. 22,23 The relationship between sleep duration and body weight (BW) described in previous longitudinal studies, however, did not take pubertal stages into account, which might influence this relationship.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Weight and height have been measured at each assessment using calibrated scales (Landhuis, Poulton, Welch, & Hancox, 2008). BMI (kg/m 2 ) and weight (kg) at age 38 were the outcome measures.…”
Section: Smoking Statusmentioning
confidence: 99%
“…Short sleep duration in children has been associated with higher body mass index (BMI) 5 y after baseline (15). In addition, children with short sleep durations had significantly higher BMIs at 32 y of age, compared with the adult BMIs of children with moderate and long sleep durations (16). Furthermore, young teenagers with poor preschool sleep habits were more than twice as likely to use drugs, tobacco, or alcohol 10 y later (17).…”
mentioning
confidence: 99%